Pengaruh Pertumbuhan Jumlah Wisatawan Dan Investasi Terhadap Penyerapan Tenaga Kerja di Sektor Industri Pariwisata Kota Surabaya - Noviati Mahmudah; Muhammad Yasin (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Economic development is a multidimensional change process that covers various aspects and affects the quality of life and human welfare. Economic development can be approached regionally through mapping regions and growth centers (growth pools) with the aim of achieving efficient production, distribution and consumption of goods and services. Sectorally, the tourism sector is a sector that absorbs labor, captures community economic efforts, attracts tourists and brings in foreign exchange. Therefore, encouraging tourism development can create wider employment opportunities and accelerate economic growth and employment. The aim of this research is to determine the influence of the number of tourists and investment in hotels and restaurants in the tourism industry sector of the city of Surabaya. The research used quantitative descriptive with secondary data for 2014-2023 obtained from the Department of Culture, Youth and Sports and Tourism of the City of Surabaya and data from BPS. The data collected is by tabulation, analysis and also document study. The results of research using the growth rate test and also the elasticity test show that the growth in the number of tourists (X1) has no effect on labor absorption (Y). investment growth (X2) influences labor absorption (Y).